Nightchaser ebook - Bouchet, Amanda (Nightchaser, 2019)
Fans of Firefly and Star Wars can't help but fall for this sexy new paranormal romance from the author of the USA Today bestselling fantasy, THE KINGMAKER CHRONICLES. The galaxy's most wanted captain must trust her life to a charming and mysterious rogue if she doesn't want to see her latest mission go up in smoke... Tess Bailey: the galaxy's Most Wanted. Captain Tess Bailey and her ragtag crew are on the run, pursued by a tyrant who'll take them dead or alive. Her best hope is a tall, dark, and much-too-appealing stranger, Shade Ganavan. The handsome charmer claims he can help, but his motivations are far from clear... Shade Ganavan: arrogance, charm...and that special roguish something that makes you want to scream. There's no denying their chemistry, but with the dreaded Dark Watch closing in, what Tess and Shade don't know about each other might get them killed...unless they can set aside their differences and learn to trust each other before it's too late. This is no average space opera. Everyone is raving about Amanda Bouchet's Nightchaser: "Breathtakingly hot."—Booklist STARRED REVIEW "Chock-full of intrigue, heroism, conflict, and sexual tension."—Kirkus STARRED REVIEW "Out-of-this-world."—JENNIFER ESTEP, New York Times and USA Today bestselling author "Believe me when I say you need to own this book and anything Amanda Bouchet writes forever."—Kate LeBeau, Anderson's Bookshop (Naperville, IL) "Makes an early bid for one of the best titles of the year."—Entertainment Weekly